Implementation of Total Quality Management (TQM) of Curriculum Field in Khadijah Senior High School Surabaya - Romadhoni, Aulia Febri; Karwanto, Karwanto; Handayaningrum, Warih (International Journal for Educational and Vocational Studies, 2020)
This study was conducted to find out the description of the implementation of total quality management (TQM) of curriculum field in Khadijah Senior High School by paying attention to: (a) the process of disseminating the integrated quality standards in the curriculum, (b) the process of establishing an integrated quality assurance standard in the curriculum, (c) the implementation process and fulfillment of integrated quality standards in the curriculum, and (d) the process of monitoring and evaluating the assurance of integrated quality standards in the curriculum. The method used is qualitative research because it aims to obtain in-depth data and information, so that the goal to know the implementation process of integrated quality assurance in the curriculum can be achieved. This research used case study type. A research that uses this type of case study will uncover the phenomenon that exists by collecting and using as many data as possible about the thing under study. Researchers used this type of case study because they want to investigate and uncover cases effectively; then, they present them systematically. The subjects in this study were the Principal as a stakeholder who set the quality guidelines in Khadijah Senior High School Surabaya, the Deputy Principals in particular in the field of curriculum who participated in the process of setting the quality guidelines for Khadijah Senior High School, the school committee, the Quality Assurance Unit, the teachers as the executor and the student's parents as a service customer. This research was conducted in the odd semester of the 2019-2020. Data collection techniques used observation, interviews, and documentation. The data analysis technique used in this study was an interactive analysis model consisting of three components, namely data condensation, data triangulation, data presentation and conclusion making. The conclusion of this study states that each stage of total quality management (TQM) implemented in the curriculum field runs well because of the smooth coordination between the curriculum team, UPM and teachers as the spearhead of learning implementation.